Lost for more than 85 years—rediscovery of Channa amphibeus (McClelland, 1845), the world’s most elusive snakehead species (Teleostei, Labyrinthici, Channidae) - Praveenraj, Jayasimhan; Thackeray, Tejas; Moulitharan, Nallathambi; Vijayakrishnan, Balaji; Nanda, Gourab Kumar (Zootaxa, 2025)
The Chel Snakehead or Bora Chung, Channa amphibeus, is a large snakehead species endemic to the Himalayan region of India. Channa amphibeus was last recorded from specimens collected in the years between 1918 and 1933 (Shaw & Shebbeare 1938), leading to speculations that it may have gone extinct. Here, we report the re-discovery of the species after more than 85 years, based on three specimens collected in the year 2024, and additional photographic records. We also provide the first live image of C. amphibeus, along with biometric, and genetic data.